(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides an in-depth scholarly analysis of the narratological features of artistic time and psychological space in the short stories of Shukur Kholmirzayev. The study examines the relationship between the time of events and narrative time, subjective time, memory mechanisms, retrospection, closed and open spatial models, and their artistic functions in revealing the characters’ inner worlds. The findings demonstrate that in Kholmirzayev’s prose, time and space function not merely as compositional elements but as leading narrative categories that express the human inner world, spiritual conflicts, and psychological dramatism.